2009
DOI: 10.1097/mcc.0b013e328331575b
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion therapy in hemorrhagic shock

Abstract: Purpose of review Bleeding and death from hemorrhage remain a leading cause of morbidity and mortality in the trauma population. Early resuscitation of these gravely injured patients has changed significantly over the past several years. The concept of damage control resuscitation has expanded significantly with the experience of the US military in southwest Asia. This review will focus on this resuscitation strategy of transfusing blood products (red cells, plasma, and platelets) early and often in the exsang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 63 publications
1
40
0
Order By: Relevance
“…The patients with hemorrhagic shock also had a higher rate of intensive care unit admission (21 of 29 vs four of 23 patients, P , .01), ( 30 ). This is because even major occult bleeding may occur during the early phases after trauma without being recognized owing to the complex triage and screening procedures in overcrowded EDs.…”
Section: Resultsmentioning
confidence: 95%
“…The patients with hemorrhagic shock also had a higher rate of intensive care unit admission (21 of 29 vs four of 23 patients, P , .01), ( 30 ). This is because even major occult bleeding may occur during the early phases after trauma without being recognized owing to the complex triage and screening procedures in overcrowded EDs.…”
Section: Resultsmentioning
confidence: 95%
“…It has also been proposed that a delay in blood transfusion results in coagulopathy and organ failure [17]. Bonnet and colleagues reported that a delay in blood transfusion was associated with a series of maternal deaths from postpartum hemorrhage [18].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the administration of FFP has been reliant on trust in expert opinion alone. Despite this, large quantities of FFP (>15 ml/kg body weight) are recommended in cases of massive bleeding (Ho et al 2005 ;Gajic et al 2006 ;Spahn et al 2007 ;Theusinger et al 2009 ), given that a 1:1 ratio of plasma to RBCs is connected with a decreased mortality in massively transfused trauma patients (Nunez and Cotton 2009 ).…”
Section: Blood Productsmentioning
confidence: 99%